STUDI ORGANOLOGI ALAT MUSIK BERUAS DI KELURAHAN SIANTAN TENGAH KECAMATAN PONTIANAK UTARA KOTA PONTIANAK - Ilham, Gusti Muhamad; Ismunandar, Ismunandar; Silaban, Chiristianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to investigate the process of creating Beruas musical instrument, particularly analyzing structure and playing this traditional instrument in central Siantan village, North Pontianak. The purpose of this study was to find out the structure of Beruas musical instrument and to learn how to play it properly in producing good sound. The method used in this study was descriptive method; with qualitative research forms and organology approaches. The data included the observation sheet, documentation and journals about the process of creating the musical instrument. The respondent of this study wasSuhaili, Anwar Dja'far. Besides, several interviews were conducted together with the observation and documentation activities. Researcher also took part as the main instrument in collection.Validity of the data was an extension of observation and triangulation techniques. The analysis was done during and after the data collection. Beruas musical instrument was the result of an acculturation from the Middle Eastern culture, which was found through a trade and the spread of Islam Indonesia itself, there were various forms, sizes and types of Beruas these archipelago regions. However, the researcher only focused on the organological Study of Beruas instrument in central Siantan subdistrict, North Pontianak, which was made by Suhaili. Keywords: Beruas Musical Instrument, Beruas Organology, organology study